(untitled) (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
The oil spill in Nigeria’s Niger Delta stands as one of the world’s most severe environmental disasters, involving states, multinational corporations, and local communities. This dispute highlights the complexity of resolving transboundary environmental conflicts, which require legal, diplomatic, and social approaches. This research adopts a normative juridical method to examine international dispute resolution mechanisms, the role of international organizations such as the UN and UNEP, and the challenges in their implementation. The findings indicate that while international organizations have contributed through scientific reports, mediation, and policy recommendations, their effectiveness remains limited by a lack of enforcement power and global power imbalances. This study underscores the importance of strengthening international law, empowering local communities, and fostering inclusive global collaboration for effective environmental dispute resolution.